1998
DOI: 10.1038/sj.onc.1202238
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Stat3 activity by activation of mitogen-activated protein kinase (MAPK)

Abstract: STAT proteins are activated by phosphorylation at speci®c tyrosine residue at the carboxy-terminus which is required for dimer-formation, nuclear translocation, DNA binding and transcriptional activity in cells treated with cytokines and growth factors. Recent studies have indicated that STATs are also phosphorylated by MAPK, or extracellular signal-regulated kinase (ERK) on serine. We investigated the role of ERK on the regulation of STAT activity. Here, we report that ERK2 activated by its upstream kinase, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
155
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(171 citation statements)
references
References 35 publications
15
155
0
1
Order By: Relevance
“…IL-1 inhibited IL-6-mediated Jak-Stat signaling by a rapidly inducible mechanism, and inhibition of IL-6-induced Stat3 activation was mediated by p38, a kinase that is activated by multiple inflammatory/stress factors and has been strongly implicated in driving inflammation (29,30). Previously described inducible mechanisms of inhibition of Jak-Stat signaling involve synthesis of inhibitory proteins such as SOCS (18 -20, 54), potentially target the Stat molecule itself on a conserved carboxyl-terminal serine (serine 727 in Stat3) (58,60,66), or use the ERK subfamily of MAPKs (37) or PKC␣ or PKC␦ isoforms (67). Instead, the mechanism described herein is rapid, independent of de novo expression of inhibitory molecules such as SOCS, independent of modification of Stat3 on serine 727, and occurs at least in part upstream of Stat3 in the IL-6 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-1 inhibited IL-6-mediated Jak-Stat signaling by a rapidly inducible mechanism, and inhibition of IL-6-induced Stat3 activation was mediated by p38, a kinase that is activated by multiple inflammatory/stress factors and has been strongly implicated in driving inflammation (29,30). Previously described inducible mechanisms of inhibition of Jak-Stat signaling involve synthesis of inhibitory proteins such as SOCS (18 -20, 54), potentially target the Stat molecule itself on a conserved carboxyl-terminal serine (serine 727 in Stat3) (58,60,66), or use the ERK subfamily of MAPKs (37) or PKC␣ or PKC␦ isoforms (67). Instead, the mechanism described herein is rapid, independent of de novo expression of inhibitory molecules such as SOCS, independent of modification of Stat3 on serine 727, and occurs at least in part upstream of Stat3 in the IL-6 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that phosphorylation of Stat1 and Stat3 on serine 727 enhances the transcriptional potency of tyrosinephosphorylated Stat dimers (46,61,74,76,78,79), and one study suggests that DNA binding is enhanced as well (72). However, several studies have suggested that serine phosphorylation of Stats actually suppresses tyrosine phosphorylation and DNA binding (58,60,66,80), although only one of these studies tested this directly using a mutated Stat (58). We have not excluded that serine phosphorylation of Stats may contribute to modulating Stat activity in our system, but several lines of evidence suggest that the predominant site of inhibition occurs upstream of Stats.…”
Section: Figurementioning
confidence: 99%
“…We first examined whether Isl1 affected the endogenous Stat3 transcription activity in various cell lines that were transfected with a reporter gene containing three copies of hSIE followed by the CAT gene (Jain et al, 1998). In COS-1 cells, CAT activity was increased 3.5-fold by Isl1 in unstimulated conditions, which was higher than that stimulated by EGF (3-fold).…”
Section: Isl1 Stimulates Stat3 Transcriptional Activity and Its Targementioning
confidence: 99%
“…The chloramphenicol acetyltransferase (CAT) assay was performed as described previously (Jain et al, 1998). The firefly luciferase reporter gene constructs m67-hSIE-luc and pGL3 ␣2-M 215luc were gifts from J. Bromberg (Memorial Sloan Kettering Cancer Center, New York, NY) and P. C. Heinrich (RWTH Aachen, Universitats Klinikum, Aachen, Germany), respectively.…”
Section: Reporter Gene Assaysmentioning
confidence: 99%
“…30 The regulation of this pathway by the MAP kinases appears to be extremely complex as phosphorylation of the Stats appear to be mediated by multiple components of this pathway and serine phosphorylation of the Stats have been reported to both stimulate and inhibit the transcriptional activity of these proteins. [182][183][184][185] To add another level of complexity into this pathway the Jaks have also been reported to activate the Erk kinases. 186 Stancato et al 187 report that IFN-␥ and oncostatin M both activate Raf-1.…”
Section: Jak/stat Pathwaymentioning
confidence: 99%